The CTLA4 -819 C/T Dimorphism Is Associated with Type 1 Diabetes in Egyptian Children - HM Saleh; N Rohowsky; M Leski (Tehran University of Medical Sciences, 2009)
"nBackground: We investigated whether the C-819T SNP of the CTLA4 gene is associated with Type 1 diabetes (T1D) for the Egyptian population, a multi-ethnic group.  We determined if expression of the C-819T SNP correlated with onset of T1D for Egyptian children and the prevalence of this polymorphism with respect to gender."nMethods: The association of the C-819T SNP in intron 1 of the CTLA-4 gene with T1D was investigated in 396 Egyptian patients ≤ 14 years old and 396 control subjects >24 years old, with a similar ratio of males to females in both groups.  The diagnosis of T1D was made based on ketoacidosis or ketosis with severe symptoms of acute onset at presentation and continuous dependence on insulin. Controls were negative for anti-GAD antibodies and were greater than 24 years of age.  Genotyping was performed using single strand conformation polymorphism (SSCP), temperature gradient gel electrophoresis (TGGE), polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and reverse dot blot (RDB)."nResults: The results demonstrated an association of the C-819T SNP in the CTLA-4 gene with T1D patients (P= 0.0096).  This association was more pronounced in children ≤5 years of age (P= 0.0178) than in children 6-14 years of age (P= 0.0437).  Moreover, this association was stratified by gender and age to female patients with age at onset 0-5 years old (P= 0.0186) more than male patient with the age at onset 0-5 years old (P= 0.3120)."nConclusion: The results support an association of the C-819T SNP in the CTLA-4 gene with Egyptian children, specifically, females of onset age 0-5 years old.